Oligocene Palynology Of On-Shore West Java - Eko Budi Lelono (Testing Center for Oil and Gas LEMIGAS, 2012)
Compared to its counterpart in the off-shore area (including Northwest Java and Northeast Java), the Oligocene sediment of on-shore West Java provides low pollen assemblages. In addition, superwet elements of Dacrydium and Casuarina commonly occurred in off-shore area are less represented in the on-shore area. However, it is believed that the study area still experienced wet climate condition as proved by common occurrence of rattan pollen Dicolpopollis spp. indicating a thick growth of swamp forest under moist climate. Unlike its counterpart in the off-shore North West Java, the studied sediment rarely yields lacustrine elements suggesting the disappearance of lake deposit. The Oligocene sediment of on-shore West Java is defi ned by the regular appearance of Oligocene marker of pollen Meyeripollis naharkotensis. The last occurrence of this pollen marks the top Oligocene age. In fact, the appearance of pollen M. Naharkotensis is obviously used to separate Oligocene age from Miocene age in the off-shore area. Moreover, marine micropaleontology analysis on foraminifers and calcareous nannoplankton confi rms this age. The studied sediment was deposited in the transition to shallow marine environment as indicated by rare occurrence of marine microfossils. The common brackish pollen of Zonocostites ramonae (Rizophora) and Spinizonocolpites echinatus (Nypa) indicates mangrove/ back-mangrove environment. Moreover, the domination of shallow water benthonic over the planktonic forms suggests shallow marine setting.